A Combined "Electrochemical–Frustrated Lewis Pair" Approach to Hydrogen Activation: Surface Catalytic Effects at Platinum Electrodes. Issue 2 (7th November 2014) - Lawrence, Elliot J.; Blagg, Robin J.; Hughes, David L.; Ashley, Andrew E.; Wildgoose, Gregory G.
Abstract Herein, we extend our "combined electrochemical–frustrated Lewis pair" approach to include Pt electrode surfaces for the first time. We found that the voltammetric response of an electrochemical–frustrated Lewis pair (FLP) system involving the B(C6F5)3/[HB(C6F5)3]− redox couple exhibits a strong surface electrocatalytic effect at Pt electrodes. Using a combination of kinetic competition studies in the presence of a H atom scavenger, 6‐bromohexene, and by changing the steric bulk of the Lewis acid borane catalyst from B(C6F5)3 to B(C6Cl5)3, the mechanism of electrochemical–FLP reactions on Pt surfaces was shown to be dominated by hydrogen‐atom transfer (HAT) between Pt, [PtH] adatoms and transient [HB(C6F5)3]⋅ electrooxidation intermediates. These findings provide further insight into this new area of combining electrochemical and FLP reactions, and proffers additional avenues for exploration beyond energy generation, such as in electrosynthesis.